Urgensi Perguruan Tinggi sebagai Promotor Pernikahan bagi Para Mahasiswa (Studi Perbandingan antara Indonesia dan Iran) - Muhammad Dzulfikar Syaiful Ali (Juridische : Jurnal Penelitian Hukum, 2025)
This article is written for the paradigm shift of legal sociology and explanation of ratio legist function of Tri Dharma of College for social responsibility towards the urgent problem of marriage. The method used in this writing is functional method with micro approach, namely type of legal institution and bodies of norms approach and comparison of legal policy between Indonesia and Iran. The purpose of Indonesian nation is explicitly stated in the Opening of UUD 1945. Education for students who will go through life and become the spearhead of improving the nation's morality, is certainly a priority for every university. Students and universities who are the spearhead of the struggle to improve the nation's morality should not be trapped in the pseudo slogan of freedom version of western culture, but must focus on morality and purity. Academic spaces do not only function as a channel of information and knowledge merely formally, but there needs to be an increase in spiritual and moral education. One of the improvements of the morality of society and nation is by preparing them for the formation of the smallest cells in a country. This smallest cell is an institution that we call family. In addition, universities should not only educate young people and students regarding family formation, but should also educate and make various efforts to take preventive measures against the increasing number of divorce cases in Indonesia and various moral damages that originate from family breakdown.